Implementation of the Calistung Program in Phase A at the Sekolah Penggerak Program and the Sekolah Pengimbas Program - Dian Arumsari; Slamet Subiyantoro; Budi Usodo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research was conducted at SDN Balerejo 02 Madiun as a Driving School and SDN Garon 02 Madiun as a Driving School. The research approach applied is qualitative research with a case study design. The data collection techniques used were observation, interviews and documentation. Data analysis was carried out by applying a descriptive qualitative interactive model approach through the steps of data collection, data condensation, data display, and conclusion: drawing/verifying. The research results show that the implementation of the Calistung program in phase A at Driving Schools and Imposing Schools is carried out by providing additional hours after teaching and learning activities on certain days. The implementation of the Calistung program uses contextual/real learning methods accompanied by several reading books, letter cards and number cards. The teacher also provides books that students are interested in as reading sources, introducing numbers using basic arithmetic operations. The obstacles to implementing the Calistung are difficulties in providing learning media, the use of inappropriate methods, and various types of assessments. Another obstacle is the lack of availability of suitable books.